Pembelajaran Inovatif untuk Meningkatkan Minat Belajar Bahasa Inggris Siswa Sekolah Dasar di Desa Kuwum, Kabupaten Badung - Ni Nyoman Arini; Anggreni, Ni Putu Yunik; Virgia Ratna Devi; Jayanti Kumala Dewi, I Dewa Ayu Riskya; Ni Made Yulia Chrisanti; I Putu Ardimahada; Krisna Atmaja, Ida Bagus Gede Bayu; Kadek Erna Parniti; Supradnyani, Ni Putu Intan; Adi Ananta, I Putu Wahyu; Hadi Swarna, I Made Rudi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Increasing interest in learning English among primary school students is essential to support the growth of tourism in Kuwum Village. Innovative learning methods applied to increase students' interest and ability in learning English include learning while playing or educational games, making mading, making pencil case crafts, piggy bank crafts, photo frame crafts, coloring activities, and putting together puzzles. One of the biggest challenges in teaching English to elementary school students is keeping students engaged and motivated. This activity aims to increase literacy, students' interest in learning English, and develop innovative learning models. The results obtained during the teaching activities are that students become more active and motivated in learning English, students become more creative in utilizing used goods, and are able to cooperate with their friends in putting together puzzles. This innovative learning activity is able to increase students' motivation in learning English at SD Desa Kuwum. The Triatma Mulya University Thematic Community Service (KKN) team has implemented interactive and interesting teaching methods, providing a conducive learning environment, and adapting learning to students' interests and needs.